EFL UNDERGRADUATE STUDENTS’ ONLINE SELF-REGULATED LEARNING STRATEGIES DURING COVID-19 PANDEMIC - Genti Putri Dwi Redjeki; Astri Hapsari (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2022)
This research aims to identify online self-regulated learning strategies of EFL undergraduate students during the COVID-19 pandemic. This research involved 81 EFL undergraduate students batch 2020 majoring in English Language Education in a private university in Indonesia. The Online Self-Regulated English Learning (OSEL) questionnaire adapted from (Zheng et al., 2016) was chosen as the instrument of this research. The questionnaire consists of 21 items. The findings reveal that EFL undergraduate students’ online self-regulated learning strategies employ five domains, namely (1) goal setting (M= 3.800, SD= 0.890), (2) environment structuring (M= 4.015, SD= 1.033), (3) task strategies and time management (M= 3.365, SD= 1.062), (4) help-seeking (M= 3.827, SD= 1.081), and (5) self-evaluation (M= 3.784, SD= 0.968). EFL undergraduate students also perform high self-regulated learning strategies in the domain of environment structuring, particularly in arranging and determining the right place that supports learning English. However, they have low self-regulated learning strategies in task strategies and time management domains, particularly in preparing questions when learning English. Further researchers are recommended to look into the relationship between the amount of time undergraduate students spend learning English and their self-regulated learning strategies.